2021
DOI: 10.5114/aoms.2019.89254
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA H19 regulates proliferation of ovarian granulosa cells via STAT3 in polycystic ovarian syndrome

Abstract: Introduction: Studies have shown that long non-coding RNAs (lncRNA) are aberrantly expressed in polycystic ovarian syndrome (PCOS) ovaries and may have a role in PCOS development. In this study, the role and therapeutic implications of lncRNA H19 were investigated in PCOS ovaries and granulosa cells. Material and methods: qRT-PCR was used for expression analysis. Cell Counting Kit 8 (CCK-8) assay was used for cell viability and acridine orange/ ethidium bromide (AO/EB) and Annexin V/propidium iodide staining w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…Altered expression and activity of STAT3 [590], STAT1 [591] and GATA3 [592] have been demonstrated in diabetes mellitus. As previously reported, EZH2 [593] is altered expressed in polycystic ovarian syndrome. STAT3 [594], STAT1 [594] and GATA3 [595] were a diagnostic markers of multiple sclerosis and could be used as therapeutic targets.…”
Section: Discussionsupporting
confidence: 80%
“…Altered expression and activity of STAT3 [590], STAT1 [591] and GATA3 [592] have been demonstrated in diabetes mellitus. As previously reported, EZH2 [593] is altered expressed in polycystic ovarian syndrome. STAT3 [594], STAT1 [594] and GATA3 [595] were a diagnostic markers of multiple sclerosis and could be used as therapeutic targets.…”
Section: Discussionsupporting
confidence: 80%
“…LncRNA H19, the other known cancer progression biomarker [ 185 ], is also upregulated in PCOS patients and has been shown to interact with STAT3, synergistically regulating ovarian cells viability [ 186 ]. LncRNA SRA (steroid receptor RNA activator), known to be linked with several diseases and types of cancer [ 187 ], is upregulated in PCOS patients and linked to proinflammatory cytokine production (TNF-α, IL-1β and IL-6) and higher IR levels [ 188 ].…”
Section: Long Noncoding Rnas—new Regulators Of Pcos Inflammationmentioning
confidence: 99%
“…56 STATs are a family of transcription factors that mediate cytokine signaling, such as LIF, and stimulate cell proliferation. 45,57 Moreover, LIF/STAT3 pathway is reported to be involved in follicular development, 48 differentiation, 58 and cell self-renewal. 59 In the present study, we found that Hu sheep GCs were able to respond to LIF by monitoring STAT3 activation following the overexpression of LIF.…”
Section: Discussionmentioning
confidence: 99%
“…55 Additionally, increasing evidence has indicated that lncRNA or miRNA activate the LIF/STAT3 pathway to regulate cellular state and function. 57,[60][61][62] The most significant result of this study indicated that lncRNA-412.25 activated the LIF/STAT3 pathway-mediated GCs state by interacting with miR-346 in Hu sheep.…”
Section: Discussionmentioning
confidence: 99%